Fire resistance of large-scale cross-laminated timber panels - Henek, Vladan; Venkrbec, Václav; Novotný, Miloslav (IOP Publishing, 2017)
Wooden structures are increasingly being used in the construction of residential buildings. A common and often published reason to avoid wooden structures is their insufficient fire resistance, which reduces bearing capacity. For this reason, composite sandwich structures began to be designed to eliminate this drawback, as well as others. Recently, however, the trend is for a return to the original, wood-only variant and a search is underway for new technical means of improving the properties of such structures. Many timber structure technologies are known, but structures made from cross-laminated timber (CLT) panels have been used very often in recent years. CLT panels, also known as X-LAM, are currently gaining popularity in Europe. In the case of CLT panels composed of several layers of boards, they can be said to offer a certain advantage in that after the surface layer of a board has burnt and the subsurface layer has dried, oxygen is not drawn to the unburned wood for further combustion and thus the burning process ceases. CLT panels do not need to be specially modified or coated with fire resistant materials, although they are usually lined with gypsum-fiber fire resistant boards due to guidelines set out in the relevant standards. This paper presents a new method for the assessment of load-bearing perimeter walls fabricated from CLT panels without the use of an inner fire-retardant lining to ensure fire resistance at the level required by European standards (i.e. those harmonized for the Czech construction industry). The calculations were verified through laboratory tests which show that better parameters can be achieved during the classification of structures from the fire resistance point of view. The aim of the article is to utilize the results of assessment and testing by an accredited laboratory in order to demonstrate the possibilities of using CLT panels for the construction of multistorey as well as multi-purpose buildings in the Czech Republic.

Wooden structures are increasingly being used in the construction of residential buildings. A common and often published reason to avoid wooden structures is their insufficient fire resistance, which reduces bearing capacity. For this reason, composite sandwich structures began to be designed to eliminate this drawback, as well as others. Recently, however, the trend is for a return to the original, wood-only variant and a search is underway for new technical means of improving the properties of such structures. Many timber structure technologies are known, but structures made from cross-laminated timber (CLT) panels have been used very often in recent years. CLT panels, also known as X-LAM, are currently gaining popularity in Europe. In the case of CLT panels composed of several layers of boards, they can be said to offer a certain advantage in that after the surface layer of a board has burnt and the subsurface layer has dried, oxygen is not drawn to the unburned wood for further combustion and thus the burning process ceases. CLT panels do not need to be specially modified or coated with fire resistant materials, although they are usually lined with gypsum-fiber fire resistant boards due to guidelines set out in the relevant standards. This paper presents a new method for the assessment of load-bearing perimeter walls fabricated from CLT panels without the use of an inner fire-retardant lining to ensure fire resistance at the level required by European standards (i.e. those harmonized for the Czech construction industry). The calculations were verified through laboratory tests which show that better parameters can be achieved during the classification of structures from the fire resistance point of view. The aim of the article is to utilize the results of assessment and testing by an accredited laboratory in order to demonstrate the possibilities of using CLT panels for the construction of multistorey as well as multi-purpose buildings in the Czech Republic.
Fire resistance of large-scale cross-laminated timber panels
Keywords: cross-laminated timber; fire resistance; CLT; X-LAM; wooden structures; gypsum-fiber; inner lining; cross-laminated timber; fire resistance; CLT; X-LAM; wooden structures; gypsum-fiber; inner lining